Tutorials and Quiz Android application - Pakker, Sandeep Reddy (Kansas State University, 2015)
Tutorials and Quiz Android Mobile application is an application which gives you brief tutorials on various programming languages and technologies to the user who has installed this application. It gives video tutorials and training on different technologies. The mobile application also contains sample code, interview questions, and answers. This application also conducts a quiz to the user who is interested in a particular technology for checking their knowledge on the subject. It has different levels like Basic Level and Advanced Level quiz. This application conducts a quiz in the form of multiple choice questions. After the completion of the quiz the application generates reports based on the quiz conducted. The user can also test their knowledge on those technologies based on a timed quiz, we can include the above technology questions in this application. We can give a time frame for each question and all the questions are to be answered in that specified time period. Say for example we can give 20 seconds to answer a question. If the user gives an incorrect answer, will be exited out of the quiz.
Keywords: Android mobile applicationTutorials quiz android application; Computer Science (0984)